In Vitro Evaluation of ECG‐Synchronized Pulsatile Flow Using the i‐cor Diagonal Pump in Neonatal and Pediatric ECLS Systems. Issue 7 (23rd February 2018) - Moroi, Morgan; Force, Madison; Wang, Shigang; Kunselman, Allen R.; Ündar, Akif
Abstract: The objective was to assess the i‐cor electrocardiogram‐synchronized diagonal pump in terms of hemodynamic energy properties for off‐label use in neonatal and pediatric extracorporeal life support (ECLS) circuits. The neonatal circuit consisted of an i‐cor pump and console, a Medos Hilite 800 LT oxygenator, an 8Fr arterial cannula, a 10Fr venous cannula, 91 cm of 0.6‐cm ID arterial tubing, and 91 cm of 0.6‐cm ID venous tubing. The pediatric circuit was identical except it included a 12Fr arterial cannula, a 14Fr venous cannula, and a Medos Hilite 2400 LT oxygenator. Neonatal trials were conducted at 36°C with hematocrit 40% using varying flow rates (200–600 mL/min, 200 mL increments) and postarterial cannula pressures (40–100 mm Hg, 20 mm Hg increments) under nonpulsatile mode and pulsatile mode with various pulsatile amplitudes (1000–4000 rpm, 1000 rpm increments). Pediatric trials were conducted at different flow rates (800–1600 mL/min, 400 mL/min increments). Mean pressure and energy equivalent pressure increased with increasing postarterial cannula pressure, flow rate, and pulsatile amplitude. Physiologic‐like pulsatility was achieved between pulsatile amplitudes of 2000–3000 rpm. Pressure drops were greatest across the arterial cannula. Pulsatile flow generated significantly higher total hemodynamic energy (THE) levels than nonpulsatile flow. THE levels at postarterial cannula site increased with increasing postarterial cannula pressure, pulsatile amplitude, and flow rate. No surplus hemodynamic energy (SHE) was generated under nonpulsatile mode. Under pulsatile mode, preoxygenator SHE increased with increasing postarterial cannula pressure and pulsatile amplitude, but decreased with increasing flow rate. The i‐cor system can provide nonpulsatile and pulsatile flow for neonatal and pediatric ECLS. Pulsatile amplitudes of 2000–3000 rpm are recommended for use in neonatal and pediatric patients.